The Atmospheric Monitoring Strategy for the Cherenkov Telescope Array. (March 2015) - Daniel, M K
Abstract: The Imaging Atmospheric Cherenkov Technique (IACT) is unusual in astronomy as the atmosphere actually forms an intrinsic part of the detector system, with telescopes indirectly detecting very high energy particles by the generation and transport of Cherenkov photons deep within the atmosphere. This means that accurate measurement, characterisation and monitoring of the atmosphere is at the very heart of successfully operating an IACT system. The Cherenkov Telescope Array (CTA) will be the next generation IACT observatory with an ambitious aim to improve the sensitivity of an order of magnitude over current facilities, along with corresponding improvements in angular and energy resolution and extended energy coverage, through an array of Large (23 m), Medium (12 m) and Small (4 m) sized telescopes spread over an area of order ^km2. Whole sky coverage will be achieved by operating at two sites: one in the northern hemisphere and one in the southern hemisphere. This proceedings will cover the characterisation of the candidate sites and the atmospheric calibration strategy. CTA will utilise a suite of instrumentation and analysis techniques for atmospheric modelling and monitoring regarding pointing forecasts, intelligent pointing selection for the observatory operations and for offline data correction.